Unusual role of the aromatic solvent in single site Al(I) chemistry: insights from theory - Jain, Shailja; Vanka, Kumar (Chemistry - A European Journal, 2017)
The single site activation of strong σ bonds (such as that of H-H, P-H and N-H) remains a significant challenge in main group chemistry, with only a few cases reported to date. In this regard, recent exciting experiments done with Al(I) complexes hold significance, because they, too, have been seen to activate a variety of strong σ bonds. Such chemistry is generally seen to occur in aromatic solvents. The current computational studies with density functional theory (DFT) reveal the interesting reason for this: it is seen that an explicit aromatic solvent molecule acts as a catalyst by converting the Al(I) complex to Al(III) during the process. Different cases of σ bond activation by Al(I) complexes have been investigated and the efficiency for the H-X (X=H, NHtBu, PPh2) bond activation in the presence of an explicit benzene solvent molecule has been seen to be orders of magnitude higher than in its absence. The current work therefore reveals the chemistry of Al(I) complexes to be richer and more complex than realized to date, and shows it to be dependent on metal-solvent cooperativity, the first known example of its kind in main group chemistry.